"جبل نفوسة وعلماؤه في عيون مؤلّفي سير الإباضيّة وطبقاتها: الشّماخي "أنموذجا" - د. حنان الطرابلسي (Sharwes Scientific Journal, 2025)
Gebel Naffūsa represents the first geographical region that has embraced the Ibādi doctrine since the beginning of its spread out in the Maghreb. The Ibādi biographical books and their chronicles have translated for the scholars of Naffūsa and demonstrated the value of this place and its preference for the continuation of the doctrine, its popularity and the preservation of its adherents. Accordingly, we have chosen from among the books of Ibādi biography and their Maghreb chronicles "Kitāb as-aiyar” (The Book of biography) written by Abū Ahmed ibn Said Al-Shammākhi. Gebel Naffūsa was not just a geographical area which dwellers converted to the Ibādi doctrine and remained in dependence on the tenth century hegira/16th C to other centres such as Kairouan, Tāhirt and Djerba..., it was an influential area, embracing the Naffūsa tribe that made Abd Alwahāb Ibnu Rustum say "This religion has made profound by swords of Naffūsa and wealth of Mazata", an area that had a profound impact on the Ibādi history and has defined this doctrine outside the mountain, such as the island of Djerba, which embraced Ibadi Sheikhs and scholars who favoured the extension and entrenchment of the doctrine, as was the case with a Abī Masūr and his family during the 4th and 5th centuries of H/10th and 11th C.BC Discourse mechanisms used by Al-Shammākhi referring back to his homeland Gebel Naffūsa and paid tribute to his scholars and Sheikhs after the collapse of the Rustumid Imamate to become a new geographical field and another land with which new tribal ideology was established. So that, Gebel Naffūsa represented the arm of the Ibadi doctrine and its human resource from its emergence in the Maghreb to the 10th century H/ 16th C the completion date of his work.